PENGARUH INTEGRITAS AUDITOR, PEMAHAMAN GOOD GOVERNANCE, DAN BUDAYA ORGANISASI TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI PROVINSI BALI - Ni Kadek Ayu Candradewi; I Putu Deddy Samtika Putra (UNHI Press, 2022)
Auditor performance can be defined by the ability or capacity of an auditor to produce or provide audit results or findings from an audit activity based on responsibility and also financial management carried out in a particular audit team. This research is intended to be able to carry out testing how the influence of auditor integrity, understanding of good governance, and organizational culture on auditor performance. The population in this study is a Public Accounting Firm in the Province of Bali. This research is quantitative, and while the sampling technique uses purposive sampling method, with this research sample obtained and selected is 48 auditors. The analytical method used in this research is multiple linear regression analysis. The hypothesis was tested using t-test with a significance level of 5%. Based on the analysis test results simultaneously auditor integrity, understanding of good governance, and organizational culture have a significant and positive influence on auditor performance. Partially, auditor integrity, understanding of good governance, and organizational culture have a significant and positive influence on auditor performance